Engineered Human Muscle Tissue from Multilayered Aligned Myofiber Sheets for Studies of Muscle Physiology and Predicting Drug Response. Issue 2 (23rd December 2022) - Takahashi, Hironobu; Wakayama, Haruno; Nagase, Kenichi; Shimizu, Tatsuya
Abstract: In preclinical drug testing, human muscle tissue models are critical to understanding the complex physiology, including drug effects in the human body. This study reports that a multilayering approach to cell sheet‐based engineering produces an engineered human muscle tissue with sufficient contractile force suitable for measurement. A thermoresponsive micropatterned substrate regulates the biomimetic alignment of myofiber structures enabling the harvest of the aligned myofibers as a single cell sheet. The functional muscle tissue is produced by layering multiple myofiber sheets on a fibrin‐based gel. This gel environment promotes myofiber maturation, provides the tissue an elastic platform for contraction, and allows the attachment of a measurement device. Since this multilayering approach is effective in enhancing the contractile ability of the muscle tissue, this muscle tissue generates a significantly high contractile force that can be measured quantitatively. The multilayered muscle tissue shows unidirectional contraction from electrical and chemical stimulation. In addition, their physiological responses to representative drugs can be determined quantitatively in real time by changes in contractile force and fatigue resistance. These physiological properties indicate that the engineered muscle tissue can become a promising tissue model for preclinical in vitro studies in muscle physiology and drug discovery. Abstract : Cell sheet‐based tissue engineering supports production of muscle tissue that replicates muscle physiology in the human body. Since the multilayering approach enhances the contractile ability of the engineered muscle, effects of drugs are able to be determined quantitatively by changes in contractile force. Therefore, the tissue modeling system has great potential for studies of muscle physiology and for drug screening.